An eco-technoeconomic analysis of hydrogen production using solid oxide electrolysis cells that accounts for long-term degradation - Naeini, Mina; Cotton, James S.; Adams, Thomas A. (Frontiers in Energy Research, 2022)
This paper presents an eco-technoeconomic analysis (eTEA) of hydrogen production via solid oxide electrolysis cells (SOECs) aimed at identifying the economically optimal size and operating trajectories for these cells. Notably, degradation effects were accounted by employing a data-driven degradation-based model previously developed by our group for the analysis of SOECs. This model enabled the identification of the optimal trajectories under which SOECs can be economically operated over extended periods of time, with reduced degradation rate. The findings indicated that the levelized cost of hydrogen (LCOH) produced by SOECs (ranging from 2.78 to 11.67 /kg H2) is higher compared to gray hydrogen generated via steam methane reforming (SMR) (varying from 1.03 to 2.16 per kg H2), which is currently the dominant commercial process for large-scale hydrogen production. Additionally, SOECs generally had lower life cycle CO2 emissions per kilogram of produced hydrogen (from 1.62 to 3.6 kg CO2 per kg H2) compared to SMR (10.72 to 15.86 kg CO2 per kg H2). However, SOEC life cycle CO2 emissions are highly dependent on the CO2 emissions produced by its power source, as SOECs powered by high-CO2-emission sources can produce as much as 32.22 kg CO2 per kg H2. Finally, the findings of a sensitivity analysis indicated that the price of electricity has a greater influence on the LCOH than the capital cost.